2014
DOI: 10.1111/jfb.12317
|View full text |Cite
|
Sign up to set email alerts
|

Otolith microchemistry of tropical diadromous fishes: spatial and migratory dynamics

Abstract: Otolith microchemistry was applied to quantify migratory variation and the proportion of native Caribbean stream fishes that undergo full or partial marine migration. Strontium and barium water chemistry in four Puerto Rico, U.S.A., rivers was clearly related to a salinity gradient; however, variation in water barium, and thus fish otoliths, was also dependent on river basin. Strontium was the most accurate index of longitudinal migration in tropical diadromous fish otoliths. Among the four species examined, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(61 citation statements)
references
References 51 publications
6
55
0
Order By: Relevance
“…For example, Bradbury et al (2008) has reported values ~2.3 mmol/mol for Osmerus mordax (Mitchill, 1814) while Smith, Kwak (2014) reported values of ~3 mmol/mol for Gobiomorus dormitor Lacepède, 1800. However, euryhaline species were associated with significantly higher values of reference, as Mugil cephalus Linnaeus, 1758 (Sr:Ca=3.3 mmol/mol) (Fowler et al, 2016), Genidens barbus (Lacepède, 1803) (Sr:Ca=3.75 mmol/mol) (Avigliano et al, 2017b) and Zenarchopterus dunckeri Mohr, 1926 (Sr:Ca=4.2 mmol/ mol for freshwater-brackish) (Kanai et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bradbury et al (2008) has reported values ~2.3 mmol/mol for Osmerus mordax (Mitchill, 1814) while Smith, Kwak (2014) reported values of ~3 mmol/mol for Gobiomorus dormitor Lacepède, 1800. However, euryhaline species were associated with significantly higher values of reference, as Mugil cephalus Linnaeus, 1758 (Sr:Ca=3.3 mmol/mol) (Fowler et al, 2016), Genidens barbus (Lacepède, 1803) (Sr:Ca=3.75 mmol/mol) (Avigliano et al, 2017b) and Zenarchopterus dunckeri Mohr, 1926 (Sr:Ca=4.2 mmol/ mol for freshwater-brackish) (Kanai et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Each species was classified by salinity tolerance criteria and the species origin following Myers (1949a) criteria. For migratory species (sensu lato McDowall, 2008), usually sub divided in anadromous, catadromous and amphidromous (Myers, 1949b;McDowall, 2008;Acolas, Lambert, 2016), we used only the single category: diadromous; considering direct and/or indirect evidence on these species available up to the date (Cruz, 1987;Lyons, 2005;Ribeiro, Villalobos, 2010;Lorion et al, 2011;Smith, Kwak, 2014a, 2014b. Fish from marine derivation, that can be considered marine-stenohaline or marine-eurihaline (Espinosa-Pérez et al, 2011), were grouped in a single category of marine-estuarine species.…”
Section: Methodsmentioning
confidence: 99%
“…Fish from marine derivation, that can be considered marine-stenohaline or marine-eurihaline (Espinosa-Pérez et al, 2011), were grouped in a single category of marine-estuarine species. This classification was made under a bibliographic revision available for each of the species (Castro-Aguirre et al, 1999;Bussing, 2002;Lyons, 2005;Miller et al, 2009;McMahan et al, 2013;Smith, Kwak, 2014b). Some individuals were kept and deposited in the scientific collection of the Instituto de Ciencias del Mar y Limnología of the Universidad de El Salvador (ICMARES-UES 462-472, 505-538; S1 -Available only as online supplementary file accessed with the online version of the article at http://www.scielo.br/ni).…”
Section: Methodsmentioning
confidence: 99%
“…Hernández-Saavedra et al (2004) were unable to determine spawning location for Bigmouth Sleeper in the Tecolutla estuarine system of Mexico. Smith and Kwak (2014) reported that most Bigmouth Sleeper in Puerto Rico rivers were amphidromous. However, a small proportion of Puerto Rico Bigmouth Sleeper deviated from classical amphidromy (Smith and Kwak 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Smith and Kwak (2014) reported that most Bigmouth Sleeper in Puerto Rico rivers were amphidromous. However, a small proportion of Puerto Rico Bigmouth Sleeper deviated from classical amphidromy (Smith and Kwak 2014). Bacheler et al (2004) reported a self-sustaining population in Carite Reservoir, Puerto Rico, and several researchers have indicated landlocked populations in natural lakes of Honduras (Darnell 1962) and Nicaragua (McKaye et al 1979, Bedarf et al 2001).…”
Section: Introductionmentioning
confidence: 99%